'Comfort and Freedom': The Duke of Windsor's Wardrobe. (1st June 2013) - Dawson, Elizabeth
Abstract : Clothing belonging to the late Duke of Windsor (1894-1972), which remained in his Paris home until it was dispersed in 1998, provides an insight into both his taste and character. As the young and popular Prince of Wales in the 1920s, he courted notions of modernity, celebrity and informality, rejecting the stiff conventions of his father's dress and court. His innovative sense of style was emulated on both sides of the Atlantic. Throughout his life he remained loyal to the tailors and haberdashers who helped to craft his image and provide the comfort and freedom he craved in his clothes. This paper considers how some of the surviving garments in his wardrobe can help to define the man who was Prince of Wales, King Edward VIII and Duke of Windsor.